To Determine the Clinical and Mycological Profile of Fungal Keratitis - Paranjpe, Gaurav; A. Gadre, Girish; Achwal, Gargi (Journal of Coastal Life Medicine, 2023)
Aim: To determine the clinical and mycological profile of fungal keratitis. Material and methods: Each subject having infected corneal ulcers who reported in the Eye OPD got involved in the study, as well as every subject gave written informed consent. Corneal scrapings had been gathered using slit lamp magnification, then stained with gramme stain as well as ten percent KOH mount prior to being sent to Microbiology laboratory for culture as well as sensitivity testing. Fungal cultures were inoculated onto SDA, incubated at twenty seven degree celsius, checked daily, and removed after two weeks in case no growth was evident. Results: This research included 80 individuals having a clinical diagnosis of infective corneal ulcer with or without hypopyon. The majority of the cases (50.5%) were determined to be of fungal origin. The majority of the 50 patients with fungal corneal ulcers were found to be between the ages of 25 -35, and to be from rural areas. Males made up slightly more than half of all patients (54%), and most patients (60% overall) went to the hospital between 8 - 21 days after their symptoms first appeared. The most prevalent risk factor for fungal corneal ulcers was trauma with vegetative matter (40%). According to microbiological analysis, Aspergillus was the most prevalent fungus species identified (46%). Conclusion: It was observed that Aspergillus and Fusarium were the most common fungi isolated. Our hope is that by including microbiological investigation of specimens and making efficient use of available resources, we can better diagnose and treat these illnesses.